Perception of Undergraduate Students and Faculty Members Regarding the Use of Advanced Technology and Social Media in Nursing Education - Khalid Hussain; Muhammad Fayyaz Awan Awan; Munnaza Parveen Hashmi; Unaiza Pervaiz Hashmi Hashmi; Sultan Muhammad Khan (Aziz Fatimah Medical and Dental College, 2023)
The advanced digital technology is a need of the century. The Covid-19 shifted the educational world to e-learning. The closure of institutes has extensive negative implications for healthcare industry. To assess perception of undergraduate nursing students and faculty members regarding the use of advanced and social media in education, a descriptive cross-sectional study was performed at Jinnah College of Nursing, Sohail University Karachi, Pakistan from September to October 2021. 160 male and female nursing students and 20 faculty members were included after ERC approval. Two Questionnaires, one for students and another for faculty members were used.. A significant median comparison of student's perception score was found with program of nursing (p=0.011) and qualification (p=0.033).  This study describes the positive perception of nursing students and faculty members. However, proper and planned training can create significant outcomes.